Profitabilitas dampak dari likuiditas, leverage dan aktivitas - Hertina, Dede; Lase, Vici Saradede Aprillian; Syahril, Indra (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The pharmaceutical and pharmaceutical ingredients industry is one of the mainstay manufacturing sectors that is prioritized for development because it plays a major role as the main driver of the national economy. The pharmaceutical industry is a sector that is characterized by capital intensive, high technology, intensive R&D, heavily regulated, and fragmented market. Like other companies, profitability is important for the sustainability of manufacturing in the pharmaceutical industry. Profitability is a description of the company's ability to earn profits through all existing capabilities and sources such as sales activities, cash, capital, number of employees, number of branches and so on. This study aims to determine the impact of Current Ratio, Debt to Equity Ratio, and Inventory Turnover on Return On Assets in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The method of this research is quantitative method with time series data. The sampling technique used is purposive sampling technique and obtained a sample of 6 pharmaceutical companies listed on the Indonesia Stock Exchange for the period 2016-2020. The analysis technique used is multiple linear regression analysis. The results showed that the variables Current Ratio, Debt to Equity Ratio, and Inventory Turnover had an effect on Return On Assets.